Reducing Cost in RMG sector & IE as its importance Of Lithe Group - Hossain, Md. Al Mamun (Brac University, 2022)
This internship report is submitted in partial fulfillment of the requirements for the degree of Post Graduate Diploma in Knitwear Industry Management, 2021.